ANALISIS PERILAKU KEKAKUAN LANTAI STRUKTUR GEDUNG HOTEL ZEST AMBON MENGGUNAKAN METODE RESPONS SPEKTRUM - Latumeten, Victor C. M; Frans, Pieter Lourens; Hutubessy, Vector R. R. (Journal Agregate, 2023)
Earthquakes that occur can sometimes affect the structure of the building. This research was conducted to determine the effect of the earthquake on the building of the Zest Ambon hotel building which was newly build in 2018. This study aims to analyze the behavior of floor stiffness in Zest Hotel Ambon building, resulting in a large displacement value in Zest Hotel Ambon building. Data collected in this present strudy is primary data in the form of a map of the building layout, secondary data in the form of structural drawings of the zest hotel buildings. Analysis of floor stiffness and displacement of zest hotel ambon building using ETABS (Extended three analysis building systems) software with dynamic load response spectrum based on the soil site class SNI-03-1726-2019.The result of analysis showed that the deviation value between floor is still within permit limit determined by SNI-03-1726-2019and the largest amount of displacement value found on 11th floor with an X direction of 21,6 mm and a Y direction of 21,7mm where higher the floor level in the building, the greater the displacement value.